The influence of grammatical gender on the conceptualization of the world: A systematic literature review - Fatemi, S. Maryam (My University, 2024)
Many recent studies on grammatical gender and linguistic relativity overlook the neuter, simplifying the issue to a binary gender system. This study critically and systematically reviews research from the past decade, following the PRISMA protocol. The findings reveal a significant downward trend in the number of studies conducted over the past four years and a bias toward German and English. Additionally, languages with threegender systems are often inaccurately represented by excluding the neuter, limiting generalizability. These implications affect both research on linguistic relativity and genderrelated disciplines. The lack of attention to neuter gender and the recent reduction in the number of studies raise concerns about the comprehensiveness of current research approaches and highlight the need for more inclusive and refined methodologies moving forward.
Keywords: binary gender; Gender; Geschlecht; grammatical gender; linguistic relativity; PRISMA protocol; ddc:800